Instructional videos for parents/guardians of children with lip and palate clefts: integrative literature review - Débora Letícia Moreira Mendes; Lucas Gabriel Nunes Andrade; Davide Carlos Joaquim; Francisco Cezanildo Silva Benedito; Ana Caroline Rocha de Melo Leite; Virgínia Cláudia Carneiro Girão-Carmona (Elsevier, 2024)
Objective: This study aimed to review literature from the past five years, focusing on the use of educational videos as a guidance tool for parents and guardians of children with lip and palate clefts. Source of data: Conducted between April and July 2022, this integrative literature review was framed around the question: 'What is the evidence regarding the use of videos in health education for parents/guardians of children with cleft lip and palate? PICO strategy was used to develop the research. A literature search was undertaken across PubMed, Web of Science, Scopus, and the Virtual Health Library databases. Of the eight articles included in this review, four were sourced from the PubMed database, with three published in 2021. Summary of the findings: The findings indicated that YouTube videos were moderately satisfactory and met the needs of parents or legal guardians to a partial extent. The majority of the videos analyzed in this review were characterized by a moderate level of informational content. One study particularly underscored that the content of these videos only partially satisfies the requirements of the parents or legal guardians of the children. Conclusions: Nevertheless, such videos are considered viable alternatives for health education, offering numerous benefits yet facing challenges, primarily due to the scarcity of information on orofacial malformations.